Analysis of Factors Affecting the Recycling of Construction and Demolition Waste in Sharqia Governorate - El-Shimaa H. Hussein (The International Journal of Multiphysics, 2024)
Over the past decade (2015–2025), Egypt’s construction sector has grown annually at one of the fastest rates globally (around 10% annual growth) — significantly outpacing both the MENA regional average (4.5%) and the global construction industry growth rate (3.0%) according to most international construction indexes. This unprecedented growth rate has led to massive construction and demolition waste (CDW) accumulations. CDW annual generation is estimated at 40 million tons, besides accumulations from previous years estimated at around 200 million tons. Egyptian Governorates are planning an ambitious program to attract investors to establish and operate CDW recycling stations. This research investigates factors affecting CDW recycling in “Sharqia Governorate”, northeast of Egypt, as a case study. This governorate is a typical Delta province with annual construction spending of around 12.0 billion EGP and CDW generation of 3.0 million tons/year. This research aims to identify the main factors affecting the recycling of C&DW in Sharqia Governorate based on the perceptions of expert practitioners in the construction industry. The research was conducted based on a previous review of literature and expert interviews to reveal the most critical factors. Over one hundred (100) responses were received from (150) questionnaires sent to industry professionals. Respondents pointed to the importance of waste recycling in reducing construction costs using recycled materials and the need to achieve the quality of recycled materials and products. Responses also recommended the reuse of CDW in national mega projects, and the need to impose fees for the disposal of unclassified waste to encourage the establishment of CDW recycling stations. In addition to the paramount importance of training stakeholders on effective management, and to develop government incentives and to supplement the current waste management regulations to encourage the private sector to build and operate CDW recycling stations.